Identification of aurintricarboxylic acid as a potent allosteric antagonist of P2X1 and P2X3 receptors. (1st November 2019) - Obrecht, Astrid S.; Urban, Nicole; Schaefer, Michael; Röse, Anni; Kless, Achim; Meents, Jannis E.; Lampert, Angelika; Abdelrahman, Aliaa; Müller, Christa E.; Schmalzing, Günther; Hausmann, Ralf
Abstract: The homotrimeric P2X3 receptor, one of the seven members of the ATP-gated P2X receptor family, plays a crucial role in sensory neurotransmission. P2X3 receptor antagonists have been identified as promising drugs to treat chronic cough and are suggested to offer pain relief in chronic pain such as neuropathic pain. Here, we analysed whether compounds affect P2X3 receptor activity by high-throughput screening of the Spectrum Collection of 2000 approved drugs, natural products and bioactive substances. We identified aurintricarboxylic acid (ATA) as a nanomolar-potency antagonist of P2X3 receptor-mediated responses. Two-electrode voltage clamp electrophysiology-based concentration–response analysis and selectivity profiling revealed that ATA strongly inhibits the rP2X1 and rP2X3 receptors (with IC50 values of 8.6 nM and 72.9 nM, respectively) and more weakly inhibits P2X2/3, P2X2, P2X4 or P2X7 receptors (IC50 values of 0.76 μM, 22 μM, 763 μM or 118 μM, respectively). Patch-clamp analysis of mouse DRG neurons revealed that ATA inhibited native P2X3 and P2X2/3 receptors to a similar extent than rat P2X3 and P2X2/3 receptors expressed in Xenopus oocytes. In a radioligand binding assay, up to 30 μM ATA did not compete with [ 3 H]-ATP for rP2X3 receptor binding, indicating a non-competitive mechanism of action. Molecular docking studies, site-directed mutagenesis and concentration–response analysis revealed that ATA binds to the negative allosteric site of the hP2X3 receptor. In summary, ATA as a drug-like pharmacological tool compound is a nanomolar-potency, allosteric antagonist with selectivity towards αβ-methylene-ATP-sensitive P2X1 and P2X3 receptors. Highlights: P2X3R activity of 2000 approved drugs, natural products and bioactive substances. Aurintricarboxylic acid (ATA) is a nanomolar-potency antagonist of P2X1R and P2X3R. ATA as a allosteric antagonist binds to the negative allosteric site of the hP2X3R. ATA as a drug-like pharmacological tool compound fulfils Lipinski's rule of five. ATA blocks P2X3R of DRG neurons and is suitable for in vivo analysis of the P2X3R.